The school management in the LOE - Vera Mur, José María (Avances en Supervisión Educativa, 2006)
As regards school management in publicly funded state schools, the author analyses the duties, access requirements, process of selection of hope-to-be Head teachers, their appointment, support and acknowledgement. He also makes comparison about these aspects between the last two acts of education, the Organic Act of Quality in Education and the Organic Act of Education.